In vitro evaluation of the cytotoxicity and genotoxicity of resorcylidene aminoguanidine in human diploid cells B-HNF-1 - Vojtaššák, Ján; Blaško, Milan; Danišovič, Ľuboš; Čársky, Jozef; Ďuríková, Mária; Repiská, Vanda; Waczulíková, Iveta; Böhmer, Daniel (Folia biologica (Praha), 2008)
RAG belongs to appropriate inhibitors of protein glycation, i.e. formation of advanced glycation end products, which are thought to be responsible for some complications of DM, including neuropathy, angiopathy, retinopathy and nephropathy. In the present study authors have evaluated the genotoxic effect of RAG on the cell culture of human neonatal fibroblasts (B-HNF-1) in regard to its potential clinical application as inhibitor of advanced glycation end products in relationships to the pathogenesis of chronic diabetic complications. The direct contact cytotoxicity assay and micronucleus test were performed. The results showed that RAG in the concentration range of 1 x 10-4 to 1 x 10-6 mol.l-1 did not induce any changes in the morphology of exposed B-HNF-1 cells. The frequency of micronuclei was not significantly increased as well. The inhibitive effect of resorcylidene aminoguanidine was directly proportional to its concentration. It can be concluded that RAG at the selected concentrations has an inhibitive effect on proliferation of the treated cells and, at the same time, does not display any genotoxic effects on B-HNF-1 cells.
Keywords: tvar buňky; vztah mezi dávkou a účinkem léčiva; buněčné linie; Infant; Micronucleus Tests; Fibroblasts; Molecular Structure; diploidie; lidé; Cytotoxins; mutageny; fibroblasty; Cell Shape; Cell Line; molekulární struktura; Dose-Response Relationship, Drug; mikrojaderné testy; Male; cytotoxiny; kojenec; guanidiny; Diploidy; Mutagens; mužské pohlaví; Guanidines; Humans